Impact of Physical Education Facilities on Student Interest Learning at Islamic Boarding School - Supriyatni, Deswita; Sulistiadinata, Heru; Trisnasari, Winda (Journal of Physical and Outdoor Education, 2023)
The aim of this research is to describe, describe and describe the impact of physical education facilities and infrastructure on Islamic boarding school students' interest in learning. This research method uses a qualitative descriptive method with a survey approach. This research was conducted at the Tahfidz Quran Al Azhaar Ummu Suwanah Islamic Boarding School. The population in this study was class IX students of the Tahfidz Quran Al Azhaar Ummu Suwanah Islamic Boarding School. 40 The sampling technique used was purposive sampling technique. The sample in this study was 15 students and 1 PJOK teacher. The instruments used in this research were observation, interviews, closed questionnaires and documentation. Based on the results of the analysis of physical education facilities and infrastructure on Islamic boarding school students' interest in learning, it can be concluded that these facilities and infrastructure are very influential in Islamic boarding school students' interest in learning. Judging from the factors that influence their interest in learning, they tend to be external factors, namely inadequate facilities and infrastructure, the target of memorizing the Al-Quran that they have to achieve in Islamic boarding schools and busy boarding school activities which make it difficult for them to focus on studying. It is hoped that cooperation between Islamic boarding school parties and physical education teachers will try to provide the infrastructure needed for physical education learning.